Coral community structure at Celukan Bawang Reefs, Buleleng Regency, Bali Island - Widiastuti, Widiastuti; Kaigere, Daniel Tosan (Acta Aquatica: Aquatic Sciences Journal, 2022)
Celukan Bawang water has a strategic location in the northern part of Bali Island that threatened its surrounding coral reefs by shipping, power plant, industrial activities, and shrimp ponds. However, there is limited data on its biodiversity status. Therefore, it is necessary to provide factual information regarding the coral reef ecosystem condition in scientific data. This study aimed to measure the coral reef`s components and the community structure. The coverage of coral reef components was collected based on the UPT method, while community structure data was taken in a belt transect within two different sites. All data was collected in December 2020. The difference in coral reef ecosystem components among sites was analyzed with the Paired-T and Kruskal-Wallis tests (for the non-homogenous data). Results showed that the coverage of live coral colonies in Site 1 is categorized as poor, whereas Site 2 is classified as moderate. Reefs were dominated by type growth non-Acropora massive from the family of Faviidae and encrusting from the family of Pocilloporidae. Statistically, there were no significant differences in all coral reef ecosystem components among Sites 1 and 2. Diversity and Evenness Indices were similarly low in the two sites. Dominance Index demonstrated that Site 1 was lower than Site 2 (moderate). It might be related to the coverage of the abiotic component, which, despite being statistically insignificant, showed that Site 2 has a higher percentage of rubbles and rocks. Rubble and rock can be a substrate for the coral juvenile to attach.Keywords: Community structure; Coral reef; Celukan Bawang; Buleleng